Carbon black modifier and method for modifying carbon black by using carbon black modifier

By using bissulfonimide salt ionic liquid, polyamide-amine and carboxymethyl chitosan to modify the composite with carbon black, combined with microfluidic control and ultrasonic technology, the problems of high energy consumption and poor dispersion in the existing carbon black modification technology are solved, and high dispersion and excellent mechanical properties are achieved.

CN119823600AActive Publication Date: 2025-04-15青州市博奥炭黑有限责任公司

Patent Information

Application Number
CN202510322050.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

The existing carbon black modification technology has problems such as high energy consumption, large equipment wear, and excessive dispersant resulting in reduced mechanical properties, making it difficult to effectively improve the dispersion effect of carbon black.

Method used

A composite of bissulfonimide salt ionic liquid, polyamide-amine and carboxymethyl chitosan is used as a carbon black modifier. It is mixed with carbon black through a microfluidic control system, combined with ultrasonic treatment and spray drying technology to form highly dispersible carbon black.

Benefits of technology

It realizes efficient dispersion of carbon black, reduces energy consumption, avoids equipment wear, improves the binding force and mechanical properties of carbon black and the matrix, and enhances the resistance to chemical erosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a carbon black modifier and a method for modifying carbon black by using the carbon black modifier, and relates to the technical field of carbon black production, carboxymethyl chitosan, polyamide-amine and bis-sulfonimide salt ionic liquid are compounded and then subjected to microfluidic and ultrasonic treatment with carbon black, finally obtained modified carbon black is pre-cured and cross-linked, and the carbon black is prepared. The high-dispersity carbon black is finally obtained. The modification cost is low, and the dispersion effect of the carbon black is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon black production, and in particular to a carbon black modifier and a method for modifying carbon black using the carbon black modifier. Background Art

[0002] Carbon black is a black powdery substance formed by incomplete combustion or pyrolysis of hydrocarbons in the gas phase under strictly controlled process conditions. It is mainly composed of carbon and contains small amounts of elements such as oxygen, hydrogen and sulfur. The surface of carbon black particles lacks polar groups, which makes their surface inert, thus affecting their dispersibility and compatibility in the substrate. Specifically, when carbon black is added to the substrate as a reinforcing material, it will face problems such as poor compatibility with the substrate and poor particle dispersion. These shortcomings have largely restricted the scope of application of carbon black.

[0003] When modifying carbon black by mechanical dispersion method, high energy consumption, large equipment wear and tear will occur, and the long-term use cost is high. Excessive shearing may destroy the original structure of carbon black and affect its reinforcement performance. When adding dispersant for modification, excessive dispersant may occur, resulting in reduced mechanical properties such as tensile strength and aging resistance of the product, or causing defects such as precipitation and reduced gloss on the surface of the product. Summary of the invention

[0004] The first technical problem to be solved by the present invention is: in view of the deficiencies in the prior art, a carbon black modifier is provided, which has low cost and improves the dispersion effect of carbon black after use.

[0005] To solve the above-mentioned first technical problem, the technical solution of the present invention is: A carbon black modifier comprises a compound of bissulfonyl imide salt ionic liquid, polyamide-amine and carboxymethyl chitosan, wherein the mass ratio of the carboxymethyl chitosan to the bissulfonyl imide salt ionic liquid and the polyamide-amine is 1:0.2 to 1:0.5 to 2.

[0006] The second technical problem to be solved by the present invention is: to address the deficiencies in the prior art and to provide a carbon black modification method which has low cost and improves the dispersion effect of carbon black.

[0007] To solve the above second technical problem, the technical solution of the present invention is: A carbon black modification method, the preparation steps are: S01, dissolving carboxymethyl chitosan in deionized water, and stirring until the carboxymethyl chitosan is completely dissolved; S02, continue to add polyamide-amine and stir to make the polyamide-amine and carboxymethyl chitosan solution fully mixed; S03, adding bissulfonyl imide salt ionic liquid, continuing stirring, and then ultrasonicating to obtain a composite solution; S04, adding carbon black into the microfluidic system, and mixing the carbon black and the compound liquid under a pressure of 0.7-0.9 MPa to obtain a mixed liquid; S05, the mixed solution is subjected to ultrasonic treatment and then spray-dried to obtain modified carbon black; S06. The modified carbon black is pre-cured and cross-linked to finally obtain highly dispersed carbon black.

[0008] Preferably, in step S01, the mass ratio of carboxymethyl chitosan to deionized water is 1:50-100, the stirring speed is 150-300 r / min, and the stirring time is 30-60 min.

[0009] Preferably, in step S02, the stirring speed is 180-400 r / min, and the stirring time is 15-30 min.

[0010] Preferably, in step S03, the stirring speed is 200-500 r / min, the ultrasonic power is 100-300 W, and the ultrasonic time is 30-50 min.

[0011] Preferably, in step S04, the mass ratio of carbon black to compound liquid is 1:1 to 1:3.

[0012] Preferably, in step S04, the aspect ratio of the microfluidic channel is 10:1 to 15:1, and the flow rate of the microfluidic system is controlled at 1 to 3 mL / min.

[0013] Preferably, in step S05, the inlet air temperature of the spray drying is controlled at 150-200°C, and the outlet air temperature is controlled at 80-120°C.

[0014] Preferably, in step S05, the ultrasonic frequency is 20 kHz / 100 W, and the ultrasonic time is 5 to 10 s.

[0015] Preferably, in step S06, the pre-curing temperature is 80-82° C., the pre-curing time is 10-20 min, the cross-linking temperature is 120-125° C., and the cross-linking time is 15-30 min.

[0016] Due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The carboxyl groups of carboxymethyl chitosan and the amino groups of polyamide-amine form a polyelectrolyte complex through electrostatic interaction, and a multi-layer adsorption layer is constructed on the surface of carbon black. Carboxymethyl chitosan forms hydrogen bonds with the hydroxyl groups on the surface of carbon black through the carboxyl groups to provide initial anchoring. The dendritic structure of polyamide-amine prevents carbon black from agglomerating through the steric hindrance effect. At the same time, its amino group can further electrostatically bond with the anions of the bissulfonyl imide salt ionic liquid to enhance stability. After the bissulfonyl imide salt is adsorbed on the surface of carbon black, the negative charge of the anion enhances the electrostatic repulsion between carbon blacks, forming a "double insurance" with the steric hindrance of carboxymethyl chitosan / polyamide-amine, achieving dual stability of electrostatic and steric hindrance.

[0017] 2. The low surface tension of the bissulfonyl imide salt ionic liquid can quickly penetrate the microporous structure of carbon black, while the amphiphilicity (hydrophilic carboxyl group + hydrophobic skeleton) of carboxymethyl chitosan can reduce the interfacial tension between carbon black and polar matrix (such as rubber) and promote wetting. The terminal amino group of polyamide-amine can form hydrogen bonds with the cation of the bissulfonyl imide salt ionic liquid and the carboxyl group of carboxymethyl chitosan, enhancing the co-adsorption of the three on the carbon black surface and forming a uniform coating layer.

[0018] 3. Bissulfonyl imide salt ionic liquid can act as a "molecular lubricant" at high temperature to reduce the glass transition temperature (Tg) of the carboxymethyl chitosan / polyamide-amine network, so that the modified layer remains flexible during processing and avoids the dispersant from falling off due to stress concentration.

[0019] 4. Pre-curing allows carboxymethyl chitosan / polyamide-amine to initially bond through hydrogen bonds. During high-temperature cross-linking, the sulfonyl imide groups in the bissulfonyl imide salt ionic liquid can undergo condensation reactions with the hydroxyl groups of carboxymethyl chitosan and the amino groups of polyamide-amine to form a covalent bond network, which significantly improves the bonding strength between the dispersant and carbon black.

[0020] 5. Generate high-intensity shear force in the microfluidic channel to break the primary agglomerates of carbon black and form nano-scale dispersion. Compared with traditional mechanical dispersion, it has lower energy consumption and avoids excessive shearing to damage the carbon black structure, ensuring that the carbon black and the compound liquid are in full contact in the microchannel, avoiding secondary agglomeration caused by local uneven concentration.

[0021] 6. Through the synergistic triple action mechanism of interface engineering, microfluidics and ultrasound, efficient dispersion of carbon black in non-polar systems is achieved, breaking through the difficult balance between dispersibility and functionality of traditional methods, and greatly improving the dispersion uniformity in the rubber matrix. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with the embodiments. Example 1

[0023] A carbon black modification method, the preparation steps are: S01: carboxymethyl chitosan: deionized water mass ratio 1:50, stirring speed 150r / min, stirring time 30min.

[0024] S02: After adding polyamide-amine, the stirring speed is 180r / min and the stirring time is 15min.

[0025] S03: The addition amount of bissulfonyl imide salt ionic liquid is 0.2 times the mass of carboxymethyl chitosan, and the mass of polyamide-amine is 0.5 times; the stirring speed is 200r / min, the ultrasonic power is 100W, and the ultrasonic time is 30min.

[0026] S04: The mass ratio of carbon black (N330) to compound liquid is 1:1, the microfluidic pressure is 0.7 MPa, the channel aspect ratio is 10:1, and the flow rate is 1 mL / min.

[0027] S05: Ultrasonic treatment for 5 seconds, spray drying inlet air temperature of 150°C, outlet air temperature of 80°C.

[0028] S06: pre-curing temperature 80°C, time 10 min; cross-linking temperature 120°C, time 15 min, to obtain highly dispersed carbon black. Example 2

[0029] A carbon black modification method, the preparation steps are: S01: carboxymethyl chitosan: deionized water mass ratio 1:100, stirring speed 300r / min, stirring time 60min.

[0030] S02: After adding polyamide-amine, the stirring speed is 400r / min and the stirring time is 30min.

[0031] S03: The addition amount of bissulfonyl imide salt ionic liquid is 1 times the mass of carboxymethyl chitosan, and the mass of polyamide-amine is 2 times; the stirring speed is 500r / min, the ultrasonic power is 300W, and the ultrasonic time is 50min.

[0032] S04: The mass ratio of carbon black (N330) to compound liquid is 1:3, the microfluidic pressure is 0.9 MPa, the channel aspect ratio is 15:1, and the flow rate is 3 mL / min.

[0033] S05: ultrasonic treatment for 10 s, spray drying inlet air temperature of 200 °C, outlet air temperature of 120 °C.

[0034] S06: pre-curing temperature 82°C, time 20 min; cross-linking temperature 125°C, time 30 min, to obtain highly dispersed carbon black. Example 3

[0035] A carbon black modification method, the preparation steps are: S01: carboxymethyl chitosan: deionized water mass ratio 1:75, stirring speed 200r / min, stirring time 45min.

[0036] S02: After adding polyamide-amine, the stirring speed is 250r / min and the stirring time is 20min.

[0037] S03: The addition amount of bissulfonyl imide salt ionic liquid is 0.5 times the mass of carboxymethyl chitosan, and the mass of polyamide-amine is 1 times; the stirring speed is 300r / min, the ultrasonic power is 200W, and the ultrasonic time is 40min.

[0038] S04: The mass ratio of carbon black (N660) to compound liquid is 1:2, the microfluidic pressure is 0.8 MPa, the channel aspect ratio is 12:1, and the flow rate is 2 mL / min.

[0039] S05: ultrasonic treatment for 8s, spray drying inlet air temperature of 175°C, outlet air temperature of 100°C.

[0040] S06: pre-curing temperature 81°C, time 15 min; cross-linking temperature 122°C, time 20 min, to obtain highly dispersed carbon black. Example 4

[0041] A carbon black modification method, the preparation steps are: S01: carboxymethyl chitosan: deionized water mass ratio 1:80, stirring speed 250r / min, stirring time 50min.

[0042] S02: After adding polyamide-amine, the stirring speed is 300r / min and the stirring time is 25min.

[0043] S03: The addition amount of bissulfonyl imide salt ionic liquid is 0.8 times the mass of carboxymethyl chitosan, and the mass of polyamide-amine is 1.5 times; the stirring speed is 400r / min, the ultrasonic power is 250W, and the ultrasonic time is 45min.

[0044] S04: The mass ratio of carbon black (N660) to compound liquid is 1:2.5, the microfluidic pressure is 0.85 MPa, the channel aspect ratio is 13:1, and the flow rate is 2.5 mL / min.

[0045] S05: Ultrasonic treatment for 7 seconds, spray drying inlet air temperature of 180°C, outlet air temperature of 90°C.

[0046] S06: pre-curing temperature 80°C, time 18 min; cross-linking temperature 123°C, time 25 min, to obtain highly dispersed carbon black. Comparative Example 1

[0047] Only carboxymethyl chitosan was added, without adding polyamidoamine and bissulfonyl imide salt ionic liquid, and the rest of the control parameters were the same as those in Example 2, to obtain dispersed carbon black. Comparative Example 2

[0048] Only polyamide-amine was added, without adding carboxymethyl chitosan and bissulfonyl imide salt ionic liquid, and the rest of the control parameters were the same as those in Example 2, to obtain dispersed carbon black. Comparative Example 3

[0049] Only the bissulfonyl imide salt ionic liquid was added, without adding carboxymethyl chitosan and polyamide-amine, and the other control parameters were the same as those in Example 2, thereby obtaining dispersed carbon black.

[0050] The highly dispersed carbon black in Examples 1-4 and the dispersed carbon black and carbon black N330 in Comparative Examples 1-3 were taken as blank experiments to perform performance tests. The experimental results are as follows: Table 1

[0051] It can be seen from the data in the table that polyamide-amine, bissulfonyl imide salt ionic liquid and carboxymethyl chitosan significantly reduce the agglomeration of carbon black and enhance the bonding force with the matrix interface. The cross-linked structure formed with carbon black enhances the resistance to chemical corrosion. The three-dimensional network delays thermal decomposition, increases active sites and improves the adsorption effect.

[0052] It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

Claims

1. A carbon black modifier, characterized in that: The invention comprises a compound of bissulfonyl imide salt ionic liquid, polyamide-amine and carboxymethyl chitosan, wherein the mass ratio of the carboxymethyl chitosan to the bissulfonyl imide salt ionic liquid and the polyamide-amine is 1:0.2 to 1:0.5 to 2.

2. A carbon black modification method, characterized in that: The carbon black modifier according to claim 1 is prepared by the following steps: S01, dissolving carboxymethyl chitosan in deionized water, and stirring until the carboxymethyl chitosan is completely dissolved; S02, continue to add polyamide-amine and stir to make the polyamide-amine and carboxymethyl chitosan solution fully mixed; S03, adding bissulfonyl imide salt ionic liquid, continuing stirring, and then ultrasonicating to obtain a composite solution; S04, adding carbon black into the microfluidic system, and mixing the carbon black and the compound liquid under a pressure of 0.7-0.9 MPa to obtain a mixed liquid; S05, the mixed solution is subjected to ultrasonic treatment and then spray-dried to obtain modified carbon black; S06. The modified carbon black is pre-cured and cross-linked to finally obtain highly dispersed carbon black.

3. A carbon black modification method as claimed in claim 2, characterized in that: In step S01, the mass ratio of carboxymethyl chitosan to deionized water is 1:50-100, the stirring speed is 150-300 r / min, and the stirring time is 30-60 min.

4. A carbon black modification method as claimed in claim 2, characterized in that: In step S02, the stirring speed is 180-400 r / min, and the stirring time is 15-30 min.

5. A carbon black modification method as claimed in claim 2, characterized in that: In step S03, the stirring speed is 200-500 r / min, the ultrasonic power is 100-300 W, and the ultrasonic time is 30-50 min.

6. A carbon black modification method as claimed in claim 2, characterized in that: In step S04, the mass ratio of carbon black to compound liquid is 1:1 to 1:

3.

7. A carbon black modification method as claimed in claim 2, characterized in that: In step S04, the aspect ratio of the microfluidic channel is 10:1 to 15:1, and the flow rate of the microfluidic system is controlled at 1 to 3 mL / min.

8. A carbon black modification method as claimed in claim 2, characterized in that: In step S05, the inlet air temperature of the spray drying is controlled at 150-200°C, and the outlet air temperature is controlled at 80-120°C.

9. A carbon black modification method as claimed in claim 2, characterized in that: In step S05, the ultrasonic frequency is 20kHz / 100W, and the ultrasonic time is 5 to 10s.

10. A carbon black modification method as claimed in claim 2, characterized in that: In step S06, the pre-curing temperature is 80-82° C., the pre-curing time is 10-20 min, the cross-linking temperature is 120-125° C., and the cross-linking time is 15-30 min.

Citation Information

Patent Citations

  • Carboxymethyl chitosan quaternary ammonium salt / PAMAM(Polyamidoamine) core-shell nanoparticles and preparation method

    CN102604115A

  • Attapulgite clay based adsorbing material and preparation method thereof

    CN102895958A

  • Wound healing PAMAM / carboxymethyl chitosan composition, and preparation method and applications thereof

    CN106237372A

  • Polyamide-amine dendritic polymer surface modified carbon material and preparation method and application thereof

    CN113998686A

  • Amine-modified carbon black and method for producing the same

    JP2023153059A

Cited By

  • Construction process of ship cabin ground covering material

    CN120365831A

  • Construction process of a ship cabin floor covering material

    CN120365831B